The last battle of Saraighat : the story of the BJP's rise in the North-east - Sethi, Rajat; Shubhrastha (Haryana, India, Penguin Random House India Pvt. Ltd, 2017)
With special reference to Assam, India.
Includes bibliographical references (pages 175-182).
Also available as an e-book.
Keywords: Rashtriya Swayam Sevak Sangh; Bharatiya Janata Party; Hinduism and politics -- India -- Assam; Hindutva; Political campaigns -- India -- Assam; Hinduism and politics; Political campaigns; Politics and government; Assam (India) -- Politics and government; India -- Assam